ANALYSIS OF THE IMPLEMENTATION OF CORRECTIONAL DATABASE SYSTEM (CDS) AT CLASS II NARCOTICSPENITENTIARY IN BANDAR LAMPUNG - Youdi Adeputra Triawan; Baharudin Baharudin; Lintje Anna Marpaung (Universitas Labuhanbatu, 2023)
The implementation of the Correctional Database System (CDS) based on the Regulation of the Minister of Law and Human Rights (Permenkumham) Number 39 of 2016 aims to fulfillment of the rights of prisoners in prison. The purpose of this study are to analize the implementation of the CDS at the Class II Narcotics Penitentiary in Bandar Lampung and inhibiting factors for the implementation of the CDS at the Class II Narcotics Penitentiary in Bandar Lampung?Â The research using normative and juridical approach.Â The results of this study indicate that implementation of CDS at the Class II Narcotics Prison as an effort to ensure the fulfillment of the rights of prisoners in prisons has been implemented although it has not been maximized because inhibiting factors are still present. Implementation of CDS can help determine decisions such as in granting conditional leave, leave before release, parole, leave to visit family, because the calculation, registration and register f are included in it. These data are integrated between sections in the Class II Narcotics Prison in Bandar Lampung and are connected with other relevant agencies in fulfilling the rights of prisoners. The inhibiting factor for implementing CDS substantially is the sending of data from the Technical Implementing Unit to the Director General of Corrections which is still often illegible. In addition, there are still some prisoners whose files are incomplete from the Police and the Prosecutor's office which makes the remission proposal impossible. The technical obstacle is the unstable internet network so that it becomes an obstacle in providing services to the inmates.Keywords: Implementation of CDS, Rights, Prisoners.